Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12890-019-0840-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of ivacaftor in late diagnosed cystic fibrosis monozygotic twins heterozygous for F508del and R117H-7T – a case report

Abstract: Background CFTR modulator therapy with ivacaftor is a treatment option for Cystic Fibrosis (CF) patients with at least one copy of a R117H-7T mutation in the CFTR gene. Desirable effects of this therapy are improvement of lung function, decrease in exacerbation rate, normalization or reduction of sweat chloride and weight gain. Monogenetic CF-twins carry identical genetic information, so therapy response and side effects are expected to be nearly identical under this specific therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Fourteen (26%) of the observational studies focused on patients with severe airflow obstruction, defined as ppFEV 1 < 40%; in 11 of these studies, patients accessed the CFTR modulator via a compassionate access program (also referred to as a “managed access”, “early access’, “expanded access”, or “named patient” program) through the manufacturer [ 25 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Twenty (65%) of the full manuscripts were deemed to have safety as a primary focus or outcome [ 27 , 28 , 29 , 30 , 32 , 33 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen (26%) of the observational studies focused on patients with severe airflow obstruction, defined as ppFEV 1 < 40%; in 11 of these studies, patients accessed the CFTR modulator via a compassionate access program (also referred to as a “managed access”, “early access’, “expanded access”, or “named patient” program) through the manufacturer [ 25 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Twenty (65%) of the full manuscripts were deemed to have safety as a primary focus or outcome [ 27 , 28 , 29 , 30 , 32 , 33 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported increased bronchial and nasal secretions after initiating IVA in a patient with low lung function (baseline ppFEV 1 13.9%) prompting a severe pulmonary exacerbation, and IVA ultimately had to be discontinued due to difficulty clearing “liquefied” secretions despite decreases in dose [ 30 ]. Otherwise, respiratory AE reportedly resolved over time without changes to IVA therapy [ 30 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The described AE symptoms in cohorts were related to respiratory intolerance (3/20 F508del homozygote CF adult patients with LUM/IVA) [32]; chest tightness (2/29 F508del homozygote adult CF patients with LUM/IVA [33] and 1/14 F508del homozygote pediatric CF patients with LUM/IVA [34]); and undescribed AE (10/116 F508del homozygote CF patients ≥12 years old (yo) with LUM/IVA [35]). Finally, a case report described elevated transaminases with subsequent normalization of symptoms (1 adult CF heterozygous for F508del and R117H-7T with IVA [36]), and in another one, a breast development was reported as a rare dose-dependent AE of treatment with IVA [16]. Alternatively, a case report concerned a CF adult who discontinued LUM/IVA for respiratory dyspnea AE despite having already a half-dose reduction [37].…”
Section: Safety and Adverse Event (Aes) Of Cftr Modulator Drugsmentioning
confidence: 99%